Comprehensive analysis of type 1 fimbriae regulation in fimB‐null strains from the multidrug resistant Escherichia coli ST131 clone. Issue 6 (15th July 2016) - Sarkar, Sohinee; Roberts, Leah W.; Phan, Minh‐Duy; Tan, Lendl; Lo, Alvin W.; Peters, Kate M.; Paterson, David L.; Upton, Mathew; Ulett, Glen C.; Beatson, Scott A.; Totsika, Makrina; Schembri, Mark A.
Summary: Uropathogenic Escherichia coli (UPEC) of sequence type 131 (ST131) are a pandemic multidrug resistant clone associated with urinary tract and bloodstream infections. Type 1 fimbriae, a major UPEC virulence factor, are essential for ST131 bladder colonization. The globally dominant sub‐lineage of ST131 strains, clade C/ H 30‐R, possess an IS Ec55 insertion in the fimB gene that controls phase‐variable type 1 fimbriae expression via the invertible fimS promoter. We report that inactivation of fimB in these strains causes altered regulation of type 1 fimbriae expression. Using a novel read‐mapping approach based on Illumina sequencing, we demonstrate that 'off' to 'on' fimS inversion is reduced in these strains and controlled by recombinases encoded by the fimE and fimX genes. Unlike typical UPEC strains, the nucleoid‐associated H‐NS protein does not strongly repress fimE transcription in clade C ST131 strains. Using a genetic screen to identify novel regulators of fimE and fimX in the clade C ST131 strain EC958, we defined a new role for the guaB gene in the regulation of type 1 fimbriae and in colonisation of the mouse bladder. Our results provide a comprehensive analysis of type 1 fimbriae regulation in ST131, and highlight important differences in its control compared to non‐ST131 UPEC. Abstract : Uropathogenic E. coli ST131 strains from the globally dominant fluoroquinolone‐resistant subgroup possess an IS Ec55 insertion in the fimB gene that regulates fimS, an invertible DNA element containing the type 1 fimbriae promoter. Using fimbrial expression assays and a novel Illumina‐based read‐mapping approach, we show that fimS inversion is reduced in these strains and controlled by other recombinases. The figure highlights differences in type 1 fimbriae regulation between reference ST131 (EC958) and non‐ST131 (UTI89) strains.